Efektivitas Kompres Hangat Kunyit dan Serai terhadap Penurunan Nyeri Rematik pada Lansia - Senora , Cindy; Saputra, Andre; Mardiono, Sasono; Minata Wathan, Fika (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Rheumatoid arthritis (RA) or rheumatic pain is a chronic condition in the elderly that affects quality of life. Pharmacological therapy may cause side effects, making non - pharmacological alternatives such as herbal warm compresses safe and practical. This study aimed to determine the effectiveness of turmeric and lemongrass warm compresses in reducing rheumatic pain among the elderly at the Harapan Kita Social Home, Palembang. A pre- experimental design with a pretest–posttest without control group was applied. The sample consisted of 30 elderly respondents, divided into two groups: turmeric compress (15) and lemongrass compress (15), selected through purposive sampling. Pain intensity was measured using the Numeric Rating Scale (NRS) and analyzed with the Paired Sample T-test. Results showed a significant reduction in pain scores: from 4.67 to 3.00 in the turmeric group (p=0.000), and from 4.46 to 2.73 in the lemongrass group (p=0.000). In conclusion, both turmeric and lemongrass warm compresses are effective in reducing rheumatic pain in the elderly, with lemongrass showing slightly greater reduction.